Women and Nature in Homeira Qaderi's Dancing in the Mosque: An Afghan Mother's Letter to Her Son - Apriatin, Sri Nurul; Djohar, Hasnul Insani (UIN Syarif Hidayatullah Jakarta, 2022)
This study explores the relationship between gender and nature in Homeira Qaderi’s Dancing in the Mosque: An Afghan Mother's Letter to Her Son (2020). By engaging with gender studies and ecofeminism, this study aims to evaluate the aesthetic strategies that the author uses to portray the impact of the patriarchal system on Afghanistan Muslim women in Qaderi’s memoir. This paper discovers how the protagonist, Homeira, is depicted as the victim of a male-dominated system in multiple aspects of her life. Indeed, the memoir depicts gender discrimination and gender stereotyping that affected Homeira's life as a marginalized person for decades. Furthermore, Homeira realizes that she should become a pioneer in empowering women to resist the patriarchal system in her country through many symbols, including the symbols of nature, as literary devices. Arguably, within the patriarchal ideology, several values of nature and women as the feminine aspect are seemingly used to oppress women because of the biological aspect of women as reproducing, nurturing, and breastfeeding. To challenge this female oppression, the author uses the symbol of nature, such as wings, birds, phoenix, and spiders, to depict how Homeira’s struggles to achieve her freedom and gender justice. Indeed, the author also uses the symbol of books and stories to reveal how Homeira struggles to achieve higher education. Thus, Qaderi’s memoir complicates the ideas of gender and nature to undermine the patriarchal system in her memoir set in Afghanistan and the US.